(untitled) (Nordic Journal of Practical Theology, 2021)
Language creates reality and the words used to describe and outline the organizational map of The Church of Norway has an impact on how church practices are developed and interpretated. Analyzing two central documents involved in the process of developing a new organizational structure in The Church of Norway, this article discusses how different institutional logics plays against each other in the language used to describe the church organization. Emphasizing that institutional logics are sources of legitimacy, the article shows that Prosjekt kirkelig organisering (2021) seeks legitimacy as a responsible receiver of funding from the local municipalities. The article, while aware that context is a decisive factor in determining language and themes in the analyzed reports, concludes that The Church of Norway needs to make sure that they use a language that receives legitimacy not only from governmental institutions but also from within the Church.